2017
DOI: 10.1016/j.jssr.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

“They are So Much More Capable than What We Really Allow”: Inclusive Beliefs, Practices, and Textbook Use

Abstract: In this qualitative study I researched how five fifth-grade teachers’ beliefs in student capabilities influenced their curricular decision-making in daily activities with the History Alive! textbook. Students in the classrooms had reading levels 4–5 grades above and below grade level and included students with mild high-incidence disabilities. For four teachers, their strong beliefs determined what they did on a daily basis and matched the stated goals of the History Alive! textbook. For one teacher, the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Although Social Science was only the sixth highest combined caseload of SWDs and EBLs among all eleven content teaching areas, the only areas to have a higher combined caseload were elective areas or specialized areas where it would be reasonable to have higher combined caseloads (e.g., Health or Physical Education). While there are social studies scholars that examine SWDs and EBLs (Burkholdt, 2017;Courtade, Gurney, & Carden, 2017;Cruz & Thornton, 2008;De La Paz, 2005;Furgione, 2017;Gates, 2017;Hintz, 2017;Jordan, Jordan, & Hawley, 2017;Lintner, 2017;Lintner & Kumpiene, 2017;Minarik & Lintner, 2016;Morris, McGuire, & Walker, 2017;Salinas et al, 2017), the vision should be that in years to come scholars within social studies are giving these groups of students more attention to address this "demographic imperative" (Salinas et al,p. 440).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Social Science was only the sixth highest combined caseload of SWDs and EBLs among all eleven content teaching areas, the only areas to have a higher combined caseload were elective areas or specialized areas where it would be reasonable to have higher combined caseloads (e.g., Health or Physical Education). While there are social studies scholars that examine SWDs and EBLs (Burkholdt, 2017;Courtade, Gurney, & Carden, 2017;Cruz & Thornton, 2008;De La Paz, 2005;Furgione, 2017;Gates, 2017;Hintz, 2017;Jordan, Jordan, & Hawley, 2017;Lintner, 2017;Lintner & Kumpiene, 2017;Minarik & Lintner, 2016;Morris, McGuire, & Walker, 2017;Salinas et al, 2017), the vision should be that in years to come scholars within social studies are giving these groups of students more attention to address this "demographic imperative" (Salinas et al,p. 440).…”
Section: Discussionmentioning
confidence: 99%
“…A recent special issue of the Journal of Social Studies Research provided a space for scholars to examine different issues within the field of social studies as it relates to special education. The insight and studies within this edition examined such elements as: the partnership of special education and social studies (Lintner, 2017); the integration of social skills within the social studies (Morris et al, 2017); the rationales of public school alternative educators (Jordan et al, 2017); inclusive beliefs, practices, and textbook use (Hintz, 2017); how to support students with severe disabilities with read-alouds of grade-level social studies texts and systematic prompting (Courtade et al, 2017); an updated progress report about the relationship between social studies and special education (Lintner & Kumpiene, 2017); along with a variety of media reviews (Burkholdt, 2017;Furgione, 2017;Southall, 2017). This special edition was key in reminding social studies educators that there is a small but growing body of literature within the social studies that considers the needs of SWDs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The same study also found that less than 40% of these social studies teachers received professional development focused on SWD, and out of those who did receive the professional development, 34% rated it “not useful” (Mullins et al, 2020). As such, a host of special education researchers have turned their attention to designing strategies to support the diversity of learners now included in mainstream social studies classrooms (see De La Paz & MacArthur, 2003; Hintz, 2017; Jordan et al, 2017; Lintner & Kumpiene, 2017; Lintner & Schweder, 2011; Ryan et al, 2019). Unfortunately, these efforts rarely focus on civic learning or civic engagement opportunities (see Lintner, 2017).…”
Section: Literaturementioning
confidence: 99%
“…Responsibility, which is emphasized to develop in students with flipped classroom practices, is defined as follows: "The individual is to adapt, to fulfill his / her duties and to assume the consequences of the effects of his / her action on others, to respect the rights of others and to protect the consequences of his / her behavior" (Sezer, 2008, p.63). On the other hand, the upbringing of students as individuals responsible for their behaviors is important for a Social Studies class where collaborative activities take place (Hintz, 2017). This situation also manifests itself in the 2018 Social Studies Study Program (SSSP) and the textbook.…”
Section: Introductionmentioning
confidence: 99%